Microbial community dynamics of a blue-veined raw milk cheese from the UK - Yunita, Dewi; Dodd, Christine E.R. (American Dairy Science Association, 2018)
A commercial blue-veined cheese made from unpasteurized milk was examined by conventional culturing and PCR Density Gradient Gel Electrophoresis analysis of the bacterial community 16S rRNA genes using three primer sets V3, V4V5, V6V8. Genomic DNA for amplification was extracted directly from raw milk, starter culture, cheese at different stages of production, fully ripened cheese and from the cultured cells grown on various media. The outer rind was sampled separately from the inner white core and blue veins. A diverse microbiota containing Lactococcus lactis subsp. lactis, Lactobacillus plantarum, Lactobacillus curvatus, Staphylococcus gallinarum, Staphylococcus devriesei, Microbacterium sp., Sphingobacterium sp., Mycetocola sp., Brevundimonas sp., Enterococcus faecalis, Proteus sp. and Kocuria sp. was detected in the raw milk using culturing methods, but only Lactococcus lactis subsp. lactis, Lactobacillus plantarum and Enterococcus faecalis survived into the final cheese and were detected both in the core and the rind. Using PCR Density Gradient Gel Electrophoresis analysis of the cheese process samples, Staphylococcus equorum and Enterococcus durans were found in the rind of pre-piercing samples but not in the core and veins; after piercing, these species were found in all parts of the cheese but survived only in the rind when the cheese was fully ripened. Brevibacterium sp., Halomonas sp., Acinetobacter sp., Alkalibacterium sp. and Corynebacterium casei were identified only by PCR Density Gradient Gel Electrophoresis and not cultured from the samples. Brevibacterium sp. was initially identified in the cheese post piercing (core and veins), Halomonas sp. was found in the matured cheese (rind), Acinetobacter sp., Alkalibacterium sp. and Corynebacterium casei were also in the pre-piercing samples (rind) and then found through the subsequent process stages. The work suggests that in this raw milk cheese, there is a limited community from the milk surviving into the final cheese, with salt addition and handling contributing to the final cheese consortium.